Snake Venom L-Amino Acid Oxidases: Trends in Pharmacology and Biochemistry. (12th March 2014) - Izidoro, Luiz Fernando M.; Sobrinho, Juliana C.; Mendes, Mirian M.; Costa, Tássia R.; Grabner, Amy N.; Rodrigues, Veridiana M.; da Silva, Saulo L.; Zanchi, Fernando B.; Zuliani, Juliana P.; Fernandes, Carla F. C.; Calderon, Leonardo A.; Stábeli, Rodrigo G.; et al.
Abstract : L-amino acid oxidases are enzymes found in several organisms, including venoms of snakes, where they contribute to the toxicity of ophidian envenomation. Their toxicity is primarily due to enzymatic activity, but other mechanisms have been proposed recently which require further investigation. L-amino acid oxidases exert biological and pharmacological effects, including actions on platelet aggregation and the induction of apoptosis, hemorrhage, and cytotoxicity. These proteins present a high biotechnological potential for the development of antimicrobial, antitumor, and antiprotozoan agents. This review provides an overview of the biochemical properties and pharmacological effects of snake venom L-amino acid oxidases, their structure/activity relationship, and supposed mechanisms of action described so far.